Effect of polychromatic LED lighting with various red – blue ratio on the growth and development of Arabidopsis thaliana wild type plants and wei8-1tar1-1 and ahk2 mutants - Kudelina, Tatsiana N.; Krivobok, Anna S.; Bibikova, Tatiana N.; Molchan, Olga V. (Experimental Biology and Biotechnology, 2025)
The effect of polychromatic LED lighting, including all regions of the visible spectrum, with a variable (from 1 to 6) red – blue ratio (R/B) on the growth of Arabidopsis thaliana wild type plants and wei8-1tar1-1 and ahk2 mutants was studied. Under polychromatic LED lighting with a R/B = 4, A. thaliana wild type plants showed an increase in plant weight, content of photosynthetic pigments, surface density of leaves, length of the main root, and the number and length of lateral roots. A further increase in the R/B ratio to R/B = 6 did not lead to greater activation of physiological and biochemical processes. The key importance of histidine kinase AHK2 and the participation of TAA and TAR1 proteins in the stimulation of vegetative organ growth and photosynthetic apparatus formation in A. thaliana plants in response to an increase in the red level and the R/B ratio in complex polychromatic compositions was shown.